107k views
0 votes
I need help asap !!! please !!!​

I need help asap !!! please !!!​-example-1
User Ruta
by
5.5k points

1 Answer

2 votes

Answer:

2^-84

Explanation:

First simplify inside the parentheses

2^-10 / 4^2

Rewriting 4 as 2^2

2^-10 / 4^2^2

We know that a^b^c = a^(b*c)

2^-10 / 2^(2*2) = 2^-10 / 2^4

We know that a^b / a^c = a^(b-c)

2^-10 / 2^4 = 2^(-10-4) = 2^-14

Replace the term in side the parentheses with 2^-14

2^-14 ^7

We know that a^b^c = a^(b*c)

2^(-14*7)

2^-84

User Itzhaki
by
5.8k points